(untitled) (Vietnam Journal of Community Medicine, 2023)
Research objectives: Analyzing the value of cffDNA levels in non-invasive prenatal testing (NIPT) for Down syndrome. Research method and duration: A retrospective cross-sectional descriptive study on 17,451 pregnant women who received NIPT from October 2020 to July 2022. Results and conclusions: There was a positive correlation between the cffDNA concentration and the gestational week, but negatively correlated with the age of the pregnant woman in the study. Among the group of pregnant women with positive NIPT results, there was a strong positive correlation between the cffDNA concentration and z-score.